Analisis Usahatani Bawang Daun (Allium fistulosum L) di Kelurahan Landasan Ulin Utara Kecamatan Liang Anggang Kota Banjarbaru - Erma Fuzianti; Nina Budiwati; Muzdalifah Muzdalifah (AGRIDES: Jurnal Agribisnis Perdesaan, 2015)
Horticultural crops have high economic value because of its high price and short gestation period. Several vegetables can be cultivated several times in a year, mainly in tropical regions where the growing season is not restricted by winter. The study calculates the costs, revenue, income, and profit of scallioncultivation, analyze it s feasibility, and excavate the farmer problemsduring cultivation . The average total cost per farm is IDR 20,448,405.55. The farmer producesas much as 1833.33 kg per farm and generates revenue IDR 33,383,333.33 per farm . The gross revenueand profit are IDR 15,408,173 and IDR 1,934,927.78 per farm per season, in that order. The farming is feasible as the RCR is 1. 63. The field survey also identifies that resistant pests and disease infestation are the main problem. They are hardly eradicated with common pesticide.